2018
DOI: 10.1097/gox.0000000000001737
|View full text |Cite
|
Sign up to set email alerts
|

Total Endoprosthesis Versus Lundborg´s Resection Arthroplasty for the Treatment of Trapeziometacarpal Joint Osteoarthritis

Abstract: Background:There exist various operative approaches for the treatment of trapeziometacarpal joint osteoarthritis. The aim of this study was to compare the results of Lundsborg’s resection arthroplasty (RA) with implantation of a total endoprosthesis.Patients and Methods:In this 2-center study, we retrospectively analyzed 71 patients with symptomatic osteoarthritis of the carpometacarpal I joint stage III according to the Eaton-Littler classification. Thirty-two patients underwent a Lundsborg’s RA group, and 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 22 publications
0
24
0
4
Order By: Relevance
“…Quantifiable satisfaction scores were reported in seven studies, 8 , 11 , 16 , 22 , 24 , 39 , 40 and pain scores in 30 studies. 4 7 , 9 – 11 , 13 , 15 17 , 19 24 , 26 , 27 , 29 – 35 , 38 41 Comparable pre and post-operative values were reported in two studies for satisfaction, 16 , 39 and 16 studies for pain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quantifiable satisfaction scores were reported in seven studies, 8 , 11 , 16 , 22 , 24 , 39 , 40 and pain scores in 30 studies. 4 7 , 9 – 11 , 13 , 15 17 , 19 24 , 26 , 27 , 29 – 35 , 38 41 Comparable pre and post-operative values were reported in two studies for satisfaction, 16 , 39 and 16 studies for pain.…”
Section: Resultsmentioning
confidence: 99%
“…The IVORY prosthesis was reported in five studies, comprising two comparative cohorts, 21 , 22 and three descriptive cohorts, 20 , 23 , 24 with a total of 274 replacements. Two studies reported survival rates with cumulative survival analysis, demonstrating 95.5% survival at 10 years 20 and 96.4% survival at five years 21 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only subjective data almost always recorded was pain. In the 46 total implant arthroplasty articles (excluding silastic replacements) published between 2000 and 2019 (Apard and Saint-Cast, 2007; Badia and Sambandam, 2006; Brikout and Rezzouk, 2016; Brutus and Kinnen, 2004; Caekebeke and Duerinckx, 2018; Cebrian-Gomez et al., 2019; Chug et al., 2014; Cootjans et al., 2017; Craik et al., 2017; De Smet et al., 2004; Dehl et al., 2017; Dreant and Poumellec, 2019; Erne et al., 2018; Goubau et al., 2013; Guardia et al., 2010; Hansen and Vainorius, 2008; Hernández-Cortés et al., 2012; Isselin, 2001; Jacoulet, 2005; Jager et al., 2013; Johnston et al., 2012; Kaszap and Daecke, 2012; Klahn et al., 2012; Kollig et al., 2017; Krukhaug et al., 2014; Lemoine et al., 2009; Maes et al., 2010; Martin-Ferrero, 2014; Masmejean et al., 2003; Moutet et al., 2001; Pendse et al., 2009; Pérez-Ubeda et al. 2003; Regnard, 2006; Robles-Molina et al., 2017; Schuhl, 2001; Semere et al., 2015; Seng and Chantelot, 2013; Spaans et al., 2016; ten Brinke et al., 2016; Thillerman et al., 2016; Toffoli and Teissier, 2017; Ulrich-Vinther et al., 2008; Vander Eecken et al., 2012; van Rijn and Gosens, 2010; Vissers et al., 2019; Zollinger et al., 2008) functional scores were used infrequently (Table 1).…”
Section: Functional Outcomesmentioning
confidence: 99%